The impact of bicycling on PSA levels: a narrative review - Peszuk, Krzysztof; Woźniakowska , Iga; Zambrzycka, Maja; Misarko, Aleksandra; Jedwabnik, Monika; Ścigała, Stanisław; Lech, Weronika; Dobrosielska, Adrianna; Krajewski, Hoang Viet; Olszewski, Bartosz (Quality in Sport, 2026)
Background: Cycling is a widely popular form of physical activity that may influence serum prostate-specific antigen (PSA) levels, a key biomarker used in the detection and monitoring of prostate diseases. However, it remains unclear whether cycling has an effect on PSA concentrations. Aim: The aim of this review was to evaluate the effect of cycling on serum PSA levels and to identify factors that may influence changes in PSA after exercise. Material and methods: A narrative review of PubMed literature focused on the effects of cycling on PSA levels in adult men. Results: The findings were heterogeneous. Several studies reported small and transient increases in PSA levels, particularly when blood samples were collected immediately after prolonged or intensive cycling. In contrast, other studies found no significant changes in PSA concentrations. Factors such as timing of blood sampling, exercise intensity, and participant characteristics were identified as key determinants of PSA variability. Conclusions: Cycling does not appear to have a consistent or clinically significant effect on PSA levels. However, transient increases may occur under specific conditions. PSA results should therefore be interpreted with caution in individuals who have recently engaged in physical activity. Further research with standardized protocols is needed to clarify this relationship.